f(x) = 3x^2 , g(x) = 3x-1, and m(x) = 4x

Find and simplify the composition function g(m(f(x)))

answers i got which were wrong
3x-1(12x^3)
36x^4-12x^3

Maybe i am putting the information in incorrectly..

Should it look like this (3x^2(4x(3x^2))) then solve?

1 answer

m(x) = 4x, so
m(f) = 4f = 12x^2
g(x) = 3x-1, do
g(m) = 3m-1 = 36x^2-1

Using your nested notation,

g(m(f(x)) = 3(m(f(x))-1
= 3(4(f(x))-1
= 3(4(3x^2))-1
=36x^2-1
Similar Questions
  1. Several pieces of fruit are sitting on a table. What is this an example of?(1 point) Responses The composition is grounded. The
    1. answers icon 1 answer
    1. answers icon 5 answers
  2. simplifying square roots1) find volume of this prism? v=bwh b=√12" w=√6" h=√8" 2)simplify: √576 3)simplify: √400
    1. answers icon 3 answers
  3. simplifying square roots1) find volume of this prism? v=bwh b=√12" w=√6" h=√8" 2)simplify: √576 3)simplify: √400
    1. answers icon 3 answers
more similar questions